An Analysis of Frequency Distribution of LST in Iran - s.abolfazl masoodian (جغرافیا و توسعه, 2020)
Any land feature (lake, sand dune, playa, forest, …) has its own thermal properties (specific heat and thermal conductivity). So, different land features show different frequency distribution of LST. On the other hand, environmental changes affect the LST. As a result, the frequency distribution of LST over a given area may change by deforestation, desertification, drying of lakes, and disappearing of snowcaps. The high spatial and temporal resolution of MODIS LST data makes it possible to investigate the changes in the frequency distribution of LST. Using 15 years of LST data shows that the frequency distribution of LST in Iran depend on altitude, atmospheric moisture, snowcaps, surface and subsurface water respectively. Different land features such as lakes, river systems, deserts, playas, sand dunes, forest, and urban areas possess their LST frequency signature. Consequently, LST frequency distribution may be used as a powerful tool to delineate such land features. At the same time, some environmental changes like drying of lakes, deforestation and land use changes may be detected and tracked using frequency analysis of LST.